Family dysfunction and anxiety in adolescents: A moderated mediation model of self-esteem and perceived school stress. (August 2018) - Guo, Leilei; Tian, Lili; Scott Huebner, E.
Abstract: This 18-month longitudinal study examined a moderated mediation model addressing the psychosocial mechanisms that account for the association between family dysfunction and anxiety. A sample of 847 Chinese early adolescents ( M age = 12.96 years, SD = 0.67) completed questionnaires assessing family dysfunction, self-esteem, perceived school stress, and anxiety on three occasions at 6-month intervals. After gender and socioeconomic status were included as covariates, the results revealed that family dysfunction was significantly associated with adolescents' anxiety. Moreover, self-esteem partially mediated the relation between family dysfunction and anxiety, and perceived school stress moderated the mediation process in the family dysfunction to anxiety path and in the self-esteem to anxiety path. The findings suggested that both social contextual factors (e.g., family dysfunction and school stress) and self-system factors (e.g., low self-esteem) are risk factors for increased anxiety levels in adolescents. Limitations and practical applications of the study were discussed.